2020
DOI: 10.21203/rs.3.rs-17294/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Relationship between Childhood Physical Abuse and Clinical Severity of Treatment-Resistant Depression in a Geriatric Population

Abstract: Background: We assessed the correlation between childhood maltreatment (CM) and severity of depression in an elderly unipolar Treatment-Resistant Depression (TRD) sample. Methods: Patients were enrolled from a longitudinal cohort (FACE-DR) of the French Network of Expert TRD Centres. Results: Our sample included 96 patients (33% of the overall cohort) aged 60 years or above, with a mean age of 67.2 (SD = 5.7). Most of the patients were female (62.5%). The Montgomery and Asberg Depression Rating Scale (MADRS) a… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 34 publications
0
1
0
1
Order By: Relevance
“…After adjusting for significant confounding variables, the results indicated that occasional physical violence or fights, long-term physical abuse, chronic cold violence or ignorance of each other, and even persistent conflict or silent treatment to resolve the conflict were linked to one year increased risk of developing first-onset MDD. Most research on the influencing factors of depression mainly focus on the impact of direct physical trauma (Yrondi et al, 2020). Growing up and developmental stages in different types of trauma exposure could have differential effects on brain structure and function (van Rooij et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…After adjusting for significant confounding variables, the results indicated that occasional physical violence or fights, long-term physical abuse, chronic cold violence or ignorance of each other, and even persistent conflict or silent treatment to resolve the conflict were linked to one year increased risk of developing first-onset MDD. Most research on the influencing factors of depression mainly focus on the impact of direct physical trauma (Yrondi et al, 2020). Growing up and developmental stages in different types of trauma exposure could have differential effects on brain structure and function (van Rooij et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Gydymui atsparią depresiją lemia skirtingi rizikos veiksniai: pasikartojantys depresijos epizodai, ankstyva depresijos pradža (<18 metų), gretutinės ligos (koronarinė širdies liga, hipotirozė), lėtinis skausmas, vartojami medikamentai (gliukokortikoidai, interferonai), neigiami gyvenimo įvykiai [4,18]. Ligos sunkumo rodikliai, prarasta priklausomybė darbo rinkai, nemiga, migrena bei psichotropinių vaistų Atsparios depresijos gydymo strategijos pacientams, kurie nereaguoja į pradinį gydymą antidepresantais, apima gydymo sustiprinimą (angl.…”
Section: Tyrimo Rezultataiunclassified